The human body : get under the skin with science activities for kids - Reilly, Kathleen M. ("Build it yourself" series., 2019)
Provides students with a full-color guide to major systems in the human body. Also discusses the human senses, genetics, and common diseases. Includes QR codes, a timeline of medical achievements, fact boxes, a glossary, essential questions, and hands-on activities.